1986
DOI: 10.1159/000249219
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption and Psoriasis

Abstract: A study has been undertaken of the relationship between the severity of psoriasis and alcohol consumption in 100 patients with chronic plaque psoriasis. In male patients, heavy drinking, at a level liable to be detrimental to health, was found significantly more commonly in those with severe psoriasis, and alcohol-related medical or social problems were frequent. By contrast alcohol excess and alcohol-related problems were significantly less common in women irrespective of the severity of their psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 4 publications
0
31
0
1
Order By: Relevance
“…3 A related phenomenon may be heavy drinking, which in male patients with psoriasis correlates with the severity of their skin trouble and with its duration. 4 Furthermore, in a study 5 of 217 patients with psoriasis, 10% of patients reported a death wish and 6% reported active suicidal ideation at the time of the study. However, the extent of skin involvement may not be a reliable guide to disability.…”
Section: Discussionmentioning
confidence: 99%
“…3 A related phenomenon may be heavy drinking, which in male patients with psoriasis correlates with the severity of their skin trouble and with its duration. 4 Furthermore, in a study 5 of 217 patients with psoriasis, 10% of patients reported a death wish and 6% reported active suicidal ideation at the time of the study. However, the extent of skin involvement may not be a reliable guide to disability.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies have suggested that psoriasis is associated with heavy drinking, 29,30 and others 26 have found a dose-response relationship. In the present study, drinking alcohol was associated with an increased risk of psoriasis severity, but it was not statistically significant after controlling for confounding variables.…”
Section: Commentmentioning
confidence: 92%
“…The identification of prognostic factors is very important not only in selecting appropriate therapeutic approaches to individual patients, but also in understanding the natural history of the disease. Several studies have explored the prognostic factors for psoriasis [4,5,6,7]. However, the term of the follow-up period in these studies was short, 5 years or less, hence the long-term prognostic factors are still unclear.…”
Section: Introductionmentioning
confidence: 99%